Validity of a new brief assessment of apathy: Caregiver version of the apathy motivation index: Neuropsychiatry and behavioral neurology/assessment/measurement of neuropsychiatric/behavioral and psychological symptoms. (7th December 2020) - Klar, Verena S.; Ang, Yuen‐Siang; Lockwood, Patricia L.; Attaallah, Bahaaeddin; Dickson, Shannon; Drew, Daniel; Kienast, Annika; Maio, Maria R.; Plant, Olivia; Slavkova, Elitsa; Toniolo, Sofia; Zambellas, Rhea; et al.
Abstract: Background: Apathy is a common, disabling syndrome observed across neurodegenerative diseases. Self‐report of apathy from patients can be misleading so caregiver report is valuable. However, a compact instrument that does not require clinician interview, is brief but adequately detailed is lacking. Method: We developed a caregiver version of the Apathy Motivation Index (AMI CG) which requires a short 5 minute questionnaire to be completed by an informant. Scores were validated against a more extensive caregiver interview rating (Lille Apathy Rating, LARS CG), and compared to measures of depression, anhedonia, cognitive abilities, activities of daily living and caregiver burden. 124 patients (21 Alzheimer's; 45 Parkinson's; 30 limbic encephalitis; and 28 with subjective cognitive impairment) were tested. Result: The AMI CG showed good internal reliability with a significant three‐factor structure, mapping to domains of Behavioural Activation, Emotional Sensitivity and Social Motivation. It had good external validity, correlating well with other measures of apathy, but not with depression or anhedonia. A cut‐off criterion based on the LARS CG correctly classified patients as apathetic or non‐apathetic in 82% and 72% percent of cases respectively (AUC = 0.85). 20 cases identified as apathetic by the AMI CG but not the LARS CG had loss of social motivation, a dimension of apathy overlooked by traditional instruments. Patients who under‐rated their apathy compared to informants were more likely to be a greater burden to caregivers. Conclusion: The AMI CG successfully detects clinical apathy, including cases of social apathy.